Examining burden among caregivers of community-dwelling older adults in Lebanon - Zainab Barakat; Hala Sacre; Sarah Khatib; Aline Hajj; Carmela Bou Malham; Chadia Haddad; Marwan Akel; Rony M. Zeenny; Linda Abou Abbas; Marc Barakat; Pascale Salameh; Samar Rachidi (Scientific Reports)
Abstract Our study aims to describe the extent of caregiver burden and its associated factors among family caregivers of community-dwelling older adults in Lebanon in the context of multiple crises. During May–June 2024, a quantitative cross-sectional study was carried out in Lebanon involving 544 caregivers of older adults. Participants were recruited online via various social media platforms. Measures of the caregiving burden and related concepts were executed using validated scales and reports related to the care recipient’s situation. Bivariate and multivariable analyses were conducted to investigate factors associated with caregiver burden. The findings showed that most caregivers were females with lower education levels and facing financial difficulties. Among the participants, 28% reported a severe caregiving burden, 19% a moderate burden, and 24% a mild burden. The burden of caregiving was higher when the care recipient was financially dependent on the caregiver, had dementia or chronic musculoskeletal (reduced mobility) conditions, and was not able to socially integrate. The burden was also higher when the caregiver was older, lived in a remote region, was a part-time worker, had financial distress, provided care for a longer period, used maladaptive coping strategies, had no assistance, and received lower social support. This study showed that the financial difficulties of both the caregiver and the care recipient added to the usual burden of caregiving in the Lebanese context. These findings highlight the need for targeted interventions and support systems to alleviate the burden on family caregivers in Lebanon, especially given the country’s rapidly aging population, the difficult multifaceted crisis, and the limited availability of formal care services.